Um estudo sobre as armadilhas do processo decisório em fusões e aquisições - Kern, Carolina da Rocha Frigerio (2015)
Mergers and acquisitions activities, also known in the market as M&A, have been an important strategy adopted by CEOs to ensure domestic and international competitiveness, motivated by many reasons: need for growth, market share increase, entry barriers increase/growth, knowledge acquisition (human capital, tecnology and process), synergies, among others. Even though there are studies about M&A seeking for a better understanding of the problems related to strategy and decision making process alignment, critical success factors, due diligence best practices, valuations and integrations needs during the implementation of a merger or acquisition, only a few have focused on the cognitive biases of a M&A decision making process. In this way, the main purpose of this research is to present a consolidation of the main hidden traps in M&A decision making process. In a complementary manner, this study also sought the following secondary goals: understand the process of mergers and acquisitions, identify the main steps and decision points in the M&A process, analyse the traps regarding a decision making process. Therefore, it was conducted a qualitative research contemplating interviews with 15 profissionals that have had relevant participation on M&A projects of brazilian companies from different industries that have been merged, have acquired or have been acquired by another company, between 2009 and 2015. The informations obtained in the interviews were consolidated and analysed by the discourse analysis methodology. As a result, this research showed that M&A decisions are extremely complex and involve great uncertainty, which implies a bigger risk of decision traps occurrence. Among these hidden traps that have greater influence in M&A decisions, according to this study, contextualization was the one that presented the most dominance, followed by evidence of confirmation and anchoring.